Pengaruh Work Life Balance terhadap Work Engagement pada Guru SLB - Annisa Dinda Zaytuna; Dinda Dwarawati (UNISBA Press, 2024)
Abstract. Work engagement (Schaufeli and Bakker, 2004; Schaufeli, 2012) is a state of affective motivation or positive thinking in which employees feel energetic (vigor), enthusiastic (dedication), and immersed in their activities (absorption). Work life balance (Fisher et al., 2009) defines the balance between work and personal life that affects individual well-being. This study aims to determine the effect of work life balance on work engagement in special school teachers. This study used a sample of 214 permanent special school teachers. The hypothesis in this study is that work life balance has a significant effect on work engagement in special school teachers. The method used in this research is quantitative causality method using multiple linear regression analysis techniques using a sample of 214 respondents. The measuring instrument used is the Utrecht Work Engagement Scale (UWES) developed by Schaufeli and Bakker (2004) which was adapted by Kristiana et al. (2018) into a 9-item version and a work life balance measuring instrument developed by Fisher et al. (2009) which was adapted by Gunawan et al. (2019). The results of this study indicate that simultaneously, work life balance influences work engagement by 12.9%. While partially, only the Personal Life Enhancement of Work (PLEW) dimension has an influence, which is 12.7%. Abstrak. Work engagement (Schaufeli dan Bakker, 2004; Schaufeli, 2012) merupakan keadaan motivasi afektif atau pemikiran positif yang di mana karyawan merasakan energik (vigor), antusias (dedication), dan tenggelam dalam aktivitas mereka (absorption). Work life balance (Fisher et al., 2009) mendefisikan keseimbangan antara pekerjaan dan kehidupan pribadi yang berpengaruh untuk kesejahteraan individu. Penelitian ini bertujuan untuk mengetahui pengaruh work life balance terhadap work engagement pada guru Sekolah Luar Biasa (SLB). Penelitian ini menggunakan sampel guru tetap SLB sebanyak 214 orang. Hipotesis dalam penelitian ini adalah work life balance berpengaruh signifikan terhadap work engagement pada guru SLB. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif kausalitas dengan menggunakan teknik analisis regresi linear berganda yang menggunakan sampel responden sebanyak 214 orang. Alat ukur yang digunakan adalah Utrecht Work Engagement Scale (UWES) yang dikembangkan oleh Schaufeli dan Bakker (2004) yang diadaptasi oleh Kristiana et al. (2018) menjadi versi 9 item dan alat ukur work life balance yang dikembangkan oleh Fisher et al. (2009) yang diadaptasikan oleh Gunawan et al. (2019). Hasil penelitian ini menunjukkan bahwa secara simultan, work life balance memberikan pengaruh terhadap work engagement sebesar 12.9%. Sedangkan secara parsial hanya dimensi Personal Life Enhancement of Work (PLEW) memberikan pengaruh yaitu sebesar 12.7%.